Efektifitas Bridging Exercise Terhadap Keseimbangan Tubuh Pasien Stroke - Tri Wahyuni Ismoyowati; Fransisca Winandari; Agnes Toding Layuk; Aprilisa Putri Handayani; Kristina Angwarmase (FORIKES, 2022)
Stroke is an emergency condition when a neurological deficit occurs as a result of a sudden decrease in blood flow to a localized area of the brain. Based on Basic Health Research in 2018 stated that the prevalence of stroke in Indonesia by age group was more in the 55-64 years age group as much as 33.3%. The Province of the Special Region of Yogyakarta ranks second with the number of stroke patients as much as 14.6%. The highest prevalence is East Kalimantan Province with 14.7% and the lowest prevalence is Papua Province with 4.1%. The purpose of this study is to determine the effectiveness of bridging exercise on body balance of stroke patient. This study is a literature review. The databased obatained from Google Scolar, NEJM, the National Library, Pubmed, and the US of A. The keywords